2011
DOI: 10.1371/journal.pone.0022978
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Modulate Intestinal Expression of Nuclear Receptor and Provide Counter-Regulatory Signals to Inflammation-Driven Adipose Tissue Activation

Abstract: BackgroundAdipocytes from mesenteric white adipose tissue amplify the inflammatory response and participate in inflammation-driven immune dysfunction in Crohn's disease by releasing proinflammatory mediators. Peroxisome proliferator-activated receptors (PPAR)-α and -γ, pregnane x receptor (PXR), farnesoid x receptor (FXR) and liver x-receptor (LXR) are ligand-activated nuclear receptor that provide counter-regulatory signals to dysregulated immunity and modulates adipose tissue.AimsTo investigate the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 46 publications
4
72
0
2
Order By: Relevance
“…Finally, experimental colitis reduced the expression of PPAR-g in mesenteric adipose tissue, and a reduction in adipocyte diameter was observed. Creeping fat from CD patients also exhibits reduced expression of PPAR-g [30] and adipocytes from these patients have a smaller diameter than normal adipose tissue [31]. Infliximab administration was able to reverse the decrease in PPAR-g expression and improve adipocyte size to the level of control animals.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, experimental colitis reduced the expression of PPAR-g in mesenteric adipose tissue, and a reduction in adipocyte diameter was observed. Creeping fat from CD patients also exhibits reduced expression of PPAR-g [30] and adipocytes from these patients have a smaller diameter than normal adipose tissue [31]. Infliximab administration was able to reverse the decrease in PPAR-g expression and improve adipocyte size to the level of control animals.…”
Section: Discussionmentioning
confidence: 94%
“…178,179,[198][199][200] An effective treatment for CD is corresponding to modifications in MAT. For example, probiotic therapy was shown to improve the inflammation-driven metabolic dysfunction of peroxisome proliferator-activated receptors g and leptin 201 ; anti-TNF therapy was associated with modified production of adipokines and restoration of adipocyte morphology in MAT 198 ; and therapy with methotrexate resulted in diminished inflammation of MAT in an animal model. 200 Anti-TNF therapy can cause a significant increase in abdominal fat tissue.…”
Section: Mesenteric Fat In the Disease Course Of CDmentioning
confidence: 99%
“…In CD, it has some specific functions related to the maintenance of the process, such as cytokine production, adipocyte differentiation, fibrocytes differentiation inhibition, and IκB/NF-κB activation [33,52,53]. On the one hand, studies have shown a decrease of the PPAR-γ in MAT from CD patients [53,54].…”
Section: Molecular Characteristics Of the Mesenteric Adipose Tissue Imentioning
confidence: 99%
“…In CD, it has some specific functions related to the maintenance of the process, such as cytokine production, adipocyte differentiation, fibrocytes differentiation inhibition, and IκB/NF-κB activation [33,52,53]. On the one hand, studies have shown a decrease of the PPAR-γ in MAT from CD patients [53,54]. On the other hand, Desreumaux and collaborators showed that significant accumulation of intra-abdominal fat is associated with overexpression of PPAR Y and TNF-α in the MAT of the small bowel mesentery in CD patients, which suggests adipocytes as one of the sources of TNF-α production [55].…”
Section: Molecular Characteristics Of the Mesenteric Adipose Tissue Imentioning
confidence: 99%